Evaluating the combined effect of alcohol-involved and un-helmeted riding on motorcyclist fatalities in Taiwan. (August 2020) - Wiratama, Bayu Satria; Chen, Ping-Ling; Ma, Shiao-Tzu; Chen, Yi-Hua; Saleh, Wafaa; Lin, Hui-An; Pai, Chih-Wei
Highlights: National Taiwan Traffic Crash Dataset for the period from 2011 to 2015 were used in this study. Alcohol-involved and un-helmeted riders were approximately 18 times more likely to sustain fatal injuries than sober and helmeted riders. The other risk factors of motorcyclist fatalities include head-on crashes and approach-turn motorcycle crashes. Abstract: Background: Alcohol-involved riders tend to engage in other risk-taking behaviours such as un-helmeted riding which could further increases injury severity. The combined effect of alcohol-involved and un-helmeted riding on fatal injuries is rarely investigated. This study investigated the interaction effect between blood alcohol concentration and helmet use on fatal injuries. Methods: This study used the National Taiwan Traffic Crash Dataset for the period from 2011 to 2015. Data on road crashes involving a motorcycle and an automobile were extracted and analysed. Multiple logistic regression models were used to calculate the adjusted odds ratio (AOR). We calculated an interaction effect for blood alcohol concentration and helmet use based on STROBE guidelines. Results: There were a total of 669, 292 motorcyclist casualties; among these casualties, 3459 (0.5 %) motorcyclists sustained fatal injuries. Alcohol-involved riders were 9.47 times (AOR = 9.47; 95 % CI = 8.75–10.25) more likely than sober ones to sustain fatal injuries. Alcohol-involved and un-helmeted riders were approximately 18 times (AOR = 18.1; CI: 15.9–20.4) more likely to sustain fatal injuries than sober and helmeted riders. Riders involved in head-on crashes and approach-turn motorcycle crashes had an increased probability of sustaining fatal injuries by 240 % (AOR = 3.4; 95 % CI = 2.91–4.09) and 132 % (AOR = 2.3; 95 % CI = 2.016–2.67), respectively. Conclusions: This study found that alcohol-involved riding acts synergistically with un-helmeted riding to increase motorcyclist injury severity.